Psychometric Properties of the Zarit overload Scale in formal and informal caregivers of people with schizophrenia - Marchena Cárdenas, Carlos Efraín (2023)
The psychometric properties of the Zarit Caregiver Scale applied to formal and informal caregivers of people with schizophrenia in Peru were evaluated. The internal validity of the Abbreviated Zarit Scale (EZA) was evaluated using the Kuder-Richarson 21 coefficient and a value similar to the EZ scale was obtained (coefficient = ,856).The KMO adequacy measure indicates that there is a high correlation between the items (,816) as well as Bartlett's sphericity test (p<,001). A single factor explains 54.77% of the total variability of the data. In informal caregivers, the reliability of the EZ obtained high internal consistency (Cronbach's alpha coefficient=,908; Spearman-Brown coefficient=,895). The EZ applied to formal and informal caregivers obtained adequate reliability.  The EZA with a coefficient of ,879 sensitivity of 88.2% and specificity of 92.3% proved to be a recommendable instrument for assessing overload.